Moulin Volumes Regulate Subglacial Water Pressure on the Greenland Ice Sheet. Issue 20 (16th October 2020) - Covington, M. D.; Gulley, J. D.; Trunz, C.; Mejia, J.; Gadd, W.
Abstract: Meltwater inputs to moulins regulate Greenland Ice Sheet sliding speeds by controlling water pressure in the most connected regions of the subglacial drainage system. While moulin storage capacities are a critical control on subglacial water pressure, few observations exist to constrain storage. Using direct observations inside moulins, we show that moulin cross‐sectional areas can be at least 500 m 2, far greater than is observed at the surface or assumed in models. Moulin water level measurements and numerical modeling reveal that diurnal variability in moulin water pressure is highly attenuated in moulins with large storage volumes (∼3% ice pressure), relative to moulins with smaller storage volumes (∼25% ice pressure). Because large variability in moulin water pressure is linked to processes that ultimately reduce ice sliding speeds, ice sliding speeds in areas drained by large moulins may be more sensitive to long‐term increases in meltwater than areas drained by small moulins. Plain Language Summary: Each summer season on the Greenland Ice Sheet, meltwater forms stream networks on the ice surface that deliver water to moulins, which are holes in the ice that carry the water to the base of the ice sheet. When water backs up into moulins, and the water pressure beneath the ice increases, glacier sliding accelerates, leading to more rapid loss of ice into the ocean. We directly explored two moulins that contained immense storage volumes that are much larger than previously assumed to exist. Our observations of water levels inside moulins, and a model of water flow through the ice, indicate that storage of water within these large moulins during daily meltwater pulses has a big impact on how much the water pressure beneath the ice changes. Our work suggests that moulin sizes influence the interactions between summer melt and sliding of the Greenland Ice Sheet. Consequently, we need a more complete understanding of how moulin volumes vary in order to better predict how future increases in melt will impact the rate of ice loss from Greenland and to constrain its future contribution to sea level rise. Key Points: Moulin volumes on the Greenland Ice Sheet are much larger than previously thought Amplitudes of diurnal variation in moulin water level are negatively correlated with moulin volume Ice sliding speeds in areas drained by large moulins may be more sensitive to long‐term melt increases